The Use of English Songs in Spotify as Media Within the Framework TBLT on Students’ Vocabulary Mastery - Simanullang, Yudi G. (Jurnal Ilmu Multidisiplin Indonesia, 2024)
This research aimed to investigate the use of English songs in Spotify to improve students’ vocabulary at seventh grade students. It was a classroom action research conducted at SMPN 1 Singaraja involving 7th grade students of class A1. Further, this research was held in two cycles. Before the implementation of English songs the mean score students vocabulary mastery was 56.25. In the first cycle, the researcher observed an enhancement in the mastery of vocabulary, with an average score of 67.18. Subsequently, in the second cycle, a notable improvement was noted in the vocabulary mastery of compared to the preceding cycle, with an average score of 79.84. These findings underscore the profound impact of utilizing English songs on the enhancement of vocabulary mastery among seventh-grade students. These findings indicate a convincing enhancement in vocabulary mastery due to the implementation of English songs. Moreover, students exhibited heightened enjoyment, active participation, motivation, and engagement during lessons incorporating English songs for vocabulary learning. In summary, the integration of English songs via Spotify improved vocabulary mastery among seventh-grade students learning English.